EFFECT OF THE THERAPEUTIC-PREVENTIVE COMPLEX ON THE PARAMETERS OF GLUTATHIONE SYSTEM AND GLUTATHIONE-DEPENDENT ENZYMES OF THE ORAL FLUID IN CHILDREN WITH CHRONIC CATARRHAL GINGIVITIS AND DIABETES MELLITUS - L.F. Kaskova; V.A. Honcharenko (Український стоматологічний альманах)
Chronic catarrhal gingivitis (CCG) is a common stomatological disease among children suffering from diabetes mellitus. The prooxidant-antioxidant system state plays an important role in occurrence and course of chronic catarrhal gingivitis. Antioxidant protective system (AOPS) is presented by enzymatic and non-enzymatic components. Though, distribution between them is rather conditional, since the action of enzymes-antioxidants is closely connected and balanced inside and with non-enzymatic components.Glutathione system including glutathione proper and three enzymes (glutathione peroxidase – GP, glutathione reductase – GR, glutathione transferase – GT) binds free radicals, reduce oxides, lipid peroxide oxidation products, the products of membrane phospholipids, proteins, nucleic acids, and removes them from the body in the form of non-toxic conjugates.